PENGARUH EKSPEKTASI PENDAPATAN, LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Budi gautama Siregar; Aswadi Lubis (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2022)
The current condition is seen where there are still many students who have the mindset that after completing their higher education they hope to get a job in an office or company as an employee. This means that a student is said to be successful in his studies if he succeeds in working as an employee or employee. If such a mindset is still reflected in students, higher education will give birth to new unemployed people. This study aims to analyze the effect of income expectations and family environment on the interest of students of the Islamic economics study program at IAIN Padangsidimpuan to become entrepreneurs. The population of this study was students of the Islamic economics study program, Faculty of Islamic Economics and Business, Padangsidimpuan State Islamic Institute for 2018 and 2019 which amounted to 546 students. The determination of the number of samples in this study used the Slovin formula, so that 85 students were obtained consisting of 38 students from the 2018 class and 47 students from the 2019 class. Data processing was carried out using the SPSS (Software Statistical Product Service Solution) application version 22. The research findings are that income expectations and family environment have a positive and significant influence on the interest of students of Islamic economics study program to become entrepreneurs.